Development and testing of a methodology for studying types of professional and labour self-concept of people with disabilities - E. V. Istomina; T. I. Bonkalo (Вестник университета, 2025)
The ideas of people with disabilities about themselves as subjects of labour and as representatives of a certain group of professions are the subject of the study. The purpose of the study is to develop a questionnaire that allows us to determine the prevailing types of professional and labour self-concept of people with disabilities. The research has been conducted in several stages, the content of which is aimed at psychometric testing of the questionnaire, namely, testing its substantive validity, including the discriminatory ability of the items, internal consistency of its scales, correspondence of each item to the studied construct; criterion validity; construct validity of the primary testing of the methodology on a sample of 117 people with mild and moderate musculoskeletal disorders with intact intelligence aged 17 to 42 years (correlation of the questionnaire scales with the scales of other methodologies measuring similar constructs, and confirmatory factor analysis) as well as retest reliability. The primary testing of the authors’ methodology has showed its compliance with the psychometric requirements for psychological tests. The questionnaire allows identifying four types of assessments by people with disabilities of themselves as subjects of labour and as representatives of a certain group of professions: the predominance of an adequately positive assessment, pseudo-positive, indifferent and negative is revealed. Based on the combination of the assessments, it is possible to identify the prevailing type of the professional and labour self-concept: balanced and unbalanced, adaptive and maladaptive. The use of the questionnaire in the process of professional and labour orientation of people with disabilities ensures the construction of predictive models of their professional development.